Social innovation : how societies find the power to change - Mulgan, Geoff (Policy Press, 2019)
Geoff Mulgan, a pioneer in the global field of social innovation, explains how it provides answers to today's global social, economic and sustainability issues. He argues for matching R & D in technology and science with a socially focused R & D and harnessing creative imagination on a larger scale than ever before.